2017
DOI: 10.1002/1873-3468.12632
|View full text |Cite
|
Sign up to set email alerts
|

Death receptor 3 signaling enhances proliferation of human regulatory T cells

Abstract: Exploiting regulatory T cells (Tregs) to control aberrant immune reactions is a promising therapeutic approach, but is hampered by their relative paucity. In mice, activation of death receptor 3 (DR3), a member of the TNF-receptor superfamily (TNFRSF), increases Treg frequency and efficiently controls exuberant immune activation. For human Tregs, neither DR3 expression nor potential functions have been described. Here, we show that human Tregs express DR3 and demonstrate DR3-mediated activation of p38, ERK, an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
13
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 15 publications
(14 citation statements)
references
References 47 publications
1
13
0
Order By: Relevance
“…It is established that TL1A/DR3 signalling results in a generalised, non-specific stimulation of all major T cell effector pathways, for example, Th1, Th2 and Th17, which have been shown to play a pivotal role in the pathogenesis of psoriasis 18–21. In addition, recent reports suggested that DR3 signalling might also play a functional role in human T regulatory cells 22. In this study, we showed that the percentage of DR3+ PBMCs was significantly elevated in PBMCs from patients with PV compared with those from patients with AD and the control healthy volunteers.…”
Section: Discussionsupporting
confidence: 56%
“…It is established that TL1A/DR3 signalling results in a generalised, non-specific stimulation of all major T cell effector pathways, for example, Th1, Th2 and Th17, which have been shown to play a pivotal role in the pathogenesis of psoriasis 18–21. In addition, recent reports suggested that DR3 signalling might also play a functional role in human T regulatory cells 22. In this study, we showed that the percentage of DR3+ PBMCs was significantly elevated in PBMCs from patients with PV compared with those from patients with AD and the control healthy volunteers.…”
Section: Discussionsupporting
confidence: 56%
“…For predicting the percentage of Tregs in human metastatic melanoma, the LASSO regression model selected interactions involving the TNFRSF25 receptor expressed on Tregs and its ligand TNFRSF15 expressed by T helper (Th) cells as well as an interaction between PSEN1 expressed by B cells and the NOTCH2 receptor expressed on Tregs. Previous studies have shown that decreases in Notch2 expression can reduce the proportion of Tregs, whereas agonist antibodies targeting the TNFRSF25 receptor can help expand Treg populations (Bittner et al, 2017;Qin et al, 2017;Schreiber et al, 2010). Altogether, these results suggest that our approach of linking cell-cell interactions to phenotypes of interest has the potential to identify biologically relevant interactions.…”
Section: Discussionmentioning
confidence: 72%
“…For human Tregs, however, neither expression nor a potential function of DR3 have until recently been investigated. Our lab proved DR3 expression on isolated human Tregs and showed TL1A‐induced activation of MAPKs and the NFκB pathway . Furthermore, addition of TL1A during in vitro expansion increased the yield of human Treg while their suppressive capacity was retained.…”
Section: Dr3 Signaling In Immune Cellsmentioning
confidence: 80%
“…In contrast to the ubiquitous expression of its close relative TNFR1, DR3 expression is more restricted and has been reported for innate lymphoid cells (ILCs) [5][6][7], CD4+ [8][9][10][11][12] and CD8+ T cells [8,13,14], tissueresident memory T cells [15] and B cells [16,17]. Notably, T-or B-cell receptor activation can upregulate DR3 expression.…”
mentioning
confidence: 99%